Child Behavior Checklist: Socio-affective behavior questionnaire in a preschool population in Cienfuegos, Cuba. - Ramírez-Benítez, Yaser (2020)
The evaluation of socio-affective development in the child population is perceived as necessity in Cuba’s clinical and educational actions due to the low mortality levels that can result in the presence of several health risks among children; on the other hand, and in the specific case of affective problems, there are few valid and reliable tests for their early detection. Objective: To validate the Child Behavior Checklist questionnaire for a preschool population sample (4-6 years) with special needs, in the Cienfuegos province of Cuba. Material and Methods: Two samples, N1 (320 children) as a reference group to obtain percentiles and perform content validation, expert and internal consistency, and N2 (60 children) with developmental alterations to validate the percentiles and characterize future potential patients. Results: Adequate reliability values (alpha when the item is removed between .84 and .85) were found. The validity of the content indicated an adequate cultural adjustment of the questionnaire in the Cuban population, and 96.7% of the items with good and/or acceptable discrimination. In N2, 88.3% of the probands (and three fourths of them, boys) were found carrying emotional and behavioral disorders. The abnormal findings occurred, particularly, in the Introversion, Attention, Sleep and Anxiety sub-scales. Conclusions: The Child Behavior Checklist questionnaire (version for parents) is a valuable alternative for Cuban mental health professionals, as it allows classifying negative affective expressions of externalizing or internalizing type in preschool children. Studies in national reference samples must be conducted in order to test or confirm these validity and reliability findings.